Introduction and Affirmation of Car Trains in the European Union - Kamnik Zebec, Sabina; Pirš, Bojan; Maučec, Hugo (Promet - Traffic&Transportation, 2008)
We live in a time of continuous technical and technologicaldevelopment. It is the time of globalization which is the maindriver of the technological procedures in the process of executingtransport services. Railway transport in Europe requiresspecial attention, since it has a number of attributes which arenot being effectively used. Measures to reduce the use of roadnetwork have been prepared, which would consequently increaserailway transport. Individuals in personal vehicles couldreduce transport costs with the increasing use of railway transport.The introduction of car trains in Europe is also supportedby the European Union, but there has been very little done inthe European car train system. The first goal of the Europeanunion seems to be understandable : using piggyback transportto redirect as much road freight transport as possible to the Europeanrailway system. Car trains in the integrated Europeanrail system are one of numerous possibilities of how to offer auser of personal vehicle and his fellow passengers a safe, comfortable,economical and ecologically acceptable way of travelon a specific distance in the local or global sense of combinedtransport of vehicles and passengers.